Face detection in image sequence / Noor Diana Abdullah - Abdullah, Noor Diana (2007)
Face detection is to identify the image regions that contain a face regardless of its 3D position, orientation, and lighting conditions and will show the true emotions of what the person having at that time. The proposed system will be the enabling technology for many applications of facial image analysis. In this project, to gain the facial expression recognition, face detection and tracking is the first step. Once the face is detected, the particular of the face are use to track the expression. The propose method can track faces with a high degree of accuracy once they are identified. Methods of face tracking in image are compared by using Service Vector Mechine (SVM) and Successive Mean Quantization Transform (SMQT) with Matlab 7.2 as the platform to run the program. This study focused on face detecting. This quick adaptation allows the system to robustly track a face when in the image. The expected in this project will be detecting human face from the image sequences.